A STUDY OF GAMMA RAY EXPOSURE BUILDUP FACTORS IN STRATIFIED SHIELDS FOR POINT ISOTROPIC SOURCES, INCLUDING THE EFFECTS OF INCOHERENT AND COHERENT SCATTERING (Journal of Sciences, Islamic Republic of Iran)
The effects of including incoherent (bound-electron) and coherent (Rayleigh) scattering in exposure buildup factor calculations for point isotropic gamma ray sources, penetrating a two-layer water-lead shield have been investigated in the gamma ray energy (E?) range of 40 keV to 3 MeV. Incoherent scattering decreases the values of these factors in both layers up to E? ~ 200 keV and the effect is more significant in the water layer. Coherent scattering increases the factor values and is more effective in the lead layer. This effect vanishes in the water layer at E? ~ 200 keV but is present in the lead layer up to E? ~ 1,000 keV. The combined effects of both incoherent and coherent scattering have also been investigated. The combined effect increases the exposure buildup factor values. These factors are presented for different thicknesses of water and lead layers.